Transformational characteristics of ground-level ozone during high particulate events in urban area of Malaysia - Awang, Norrimi Rosaida; Ramli, Nor Azam; Shith, Syabiha; Zainordin, Nazatul Syadia; Manogaran, Hemamalini (Springer, 2018)
Observations of ground-level ozone (O3), nitric oxide (NO), nitrogen dioxide (NO2), particulate matter (PM10) and meteorological parameter (temperature, relative humidity and wind speed) fluctuations during high particulate event (HPE) and non-HPE in Malaysia have been conducted for 2 years (2013 and 2014). The study focuses on urban areas, namely, Shah Alam, Petaling Jaya and Bandaraya Melaka. The diurnal variations of ground-level O3 concentration were higher during HPE than those during non-HPE in all urban areas. The concentration of O3 fluctuated more in 2014 than 2013 due to the higher incidences of HPE. Temperature and wind speed fluctuated with higher PM10, NO2 and NO concentrations during HPE than those during non-HPE in all urban sites. Relative humidity was lower during HPE than that during non-HPE. Positive correlations were found between PM10 and ozone during HPE for Shah Alam and Petaling Jaya with 0.81 and 0.79, respectively. Meanwhile, negative correlation (− 0.76) was recorded for Bandaraya Melaka. The non-HPE correlation of PM10 and O3 showed negative values for all locations except Petaling Jaya (0.02). Temperature and wind speed shows a strong positive correlation with ozone for all locations during HPE and non-HPE with the highest at Shah Alam (0.97). Inverse relationships were found between relative humidity and O3, in which the highest was for Shah Alam (− 0.96) in 2013 and Shah Alam (− 0.97) and Bandaraya Melaka (− 0.97) in 2014. The result of the ozone best-fit equation obtained an R2 of 0.6730. The study parameters had a significant positive relationship with the ozone predictions during HPE.